Determination of Total Costs, Labour Requirements and Work Efficiencies in Second Fodder Corn Silage Production at Bafra Town of Samsun - Taner Yıldız (Turkish Journal of Agriculture: Food Science and Technology)
This study was completed with the aim of determining work efficiencies, labour requirement, and total cost of second fodder corn silage agricultural enterprises on flat ground in Bafra district of Samsun province. According to the results, total variable and fixed costs were calculated 2827.80 TL ha-1 and 4224.60 TL ha-1. The shares of variable and fixed costs in total production costs were determined 40.10% and 59.90%, respectively. Land hire had 24.70% as the highest share in fixed costs while the highest share for variable costs were observed in fertilization (10.30%) and spraying (7.00%). The highest and the lowest unit of labour requirements (units of human labour power, h ha–1) were obtained for harvesting processes (4.28 h ha-1) and spraying (2.35 h ha-1), respectively. In terms of work efficiencies, the best value was determined (0.53 ha h-1) for the transporting processes.